Redes e Investimento Directo Estrangeiro - Santos, J. Freitas; Ribeiro, J. Cadima (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2005)
The growth of inlernational competition for the reception ul Foreign Direct lnvestment (FDI) shows the interest of the countries/regions for an instrument that can channel important external resources for the economic growth. ln the attraction of FDI, relevance traditionally goes to the basic productive factors endowment of the host country/ region and the avaiable public system of incentives. Frequently, the investor's decision making process is neglected. However, in this dynamic process, it is known that different networks (social, intraorganizational, interorganizational, institutional) play a strategic mediation role in collecting , selecting and processing the information about the host countries/ regions. The estabishing and managing mechanisms of these networks are analyzed in this paper, regarding the process of FDI attraction.